A study on Bumiputera commitment in terms of time management / Fidelis Rexy Albert - Albert, Fidelis Rexy (2016)
The study aims to determine the level of commitment in time management among Bumiputera entrepreneurs. The general objective is to assess the relationship between commitment in time management and Bumiputera entrepreneurs’ business performance. There are some problem with some Bumiputera Entrepreneurs where they are not committed enough when doing business, especially in terms of time management (Lian, 2015). This study is conducted by using quantitative research method and the data collected was primarily from questionnaire. Stratified random sampling technique is used to get the population from which the respondents will be selected randomly. The study is located at mainly in Kuching Sarawak and some respondents are from Miri. The findings show that in order to improve the business performance, the Bumiputera Entrepreneurs need to put more commitment in time management. One of the recommendation is they should know how to manage themselves